155k views
6 votes
How to solve this one​

How to solve this one​-example-1
User Albertus
by
4.9k points

2 Answers

12 votes
First solve for y on one equation.

3x + y = -14

Y = -14 - 3x

Now plug this solution for y into the second equation like so:

-2x - (-14 -3x) = 9

Simplify by multiplying (-1) to the values inside of the parentheses.

-2x + 14 + 3x = 9

Simplify

X + 14 = 9

X = -5

Now use this value for x in either equation and solve

3(-5) + y = -14

-15 + y = -14

Y = 1

Check your work by adding the found x and y values into either equation.

-2(-5) - (1) = 9

10 - 1 = 9

9 = 9

X = -5
Y = 1

I am starting to do tutoring so if you would like consistent additional help make a comment and let me know
User Illuminatus
by
5.3k points
7 votes

Answer:

(-5,1)

Explanation:

Add it together

3x - 2x = x

y - y = 0

9 - 14 = -5

x = -5

Choose a random equation, doesn't matter.

3x + y = -14

3(-5) + y = -14

-15 + y = -14

y = -14 + 15

y = 1

User Christian Studer
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.